Diversity and antibacterial potential of the Actinobacteria associated with Apis mellifera ligustica - Cui, Pu; Wu, Haoyang; Jiang, Taoshan; Tao, Jian; Zhu, Zhiwei; Liu, Peng; Yu, Linsheng; Zhang, Yinglao (Frontiers in Microbiology, 2022)
Insect-associated actinobacteria are a potentially rich source of novel natural products with antibacterial activity. Here, the community composition of actinobacteria associated with Apis mellifera ligustica was investigated by integrated culture-dependent and -independent methods. A total of 61 strains of Streptomyces genera were isolated from the honeycomb, larva, and different anatomical parts of the honeybee's body using the culture-dependent method. Amplicon sequencing analyses revealed that the actinobacterial communities were dominated by the family of Bifidobacteriaceae and Microbacteriaceae in the honeybee gut, and Nocardiaceae and Pseudonocardiaceae in the honeycomb, whereas only Streptomyces genera were isolated by the culture-dependent method. Culture-independent analyses showed more diverse actinobacterial communities than those culture-dependent methods. The antibacterial bioassay showed that most crude extracts of representative isolates exhibited antibacterial activities. Among them, the crude extract of Streptomyces sp. FCF01 showed the best antibacterial activities against Staphylococcus aureus, Micrococcus tetragenus, and Pseudomonas syringae pv. actinidiae (Psa) with the disc diameter of inhibition zone diameter (IZD) of 23.00, 15.00, and 13.33 mm, respectively. Chemical analysis of Streptomyces sp. FCF01 led to the isolation of three secondary metabolites, including mayamycin (1), mayamycin B (2), and N-(2-Hydroxyphenyl) acetamide (3). Among them, compound 1 displayed strong antibacterial activity against S. aureus, M. tetragenus, and Psa with minimum inhibitory concentrations (MIC) values of 6.25, 12.5, and 6.25 µg/mL, respectively. In addition, two novel derivative compounds 1a and 1b were synthesized by acetylation of compound 1. Both compounds 1a and 1b displayed similar antibacterial activities with those of metabolite 1. These results indicated that Streptomyces species associated with honeybees had great potential in finding antibiotics.